2022
DOI: 10.3390/app13010162
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics Evaluation Using Motion Capture Technology—Literature Review

Abstract: Due to the increasingly high proportion of manual activities in production processes, there is a constant risk of musculoskeletal disorders or work-related injuries. The risk of these problems is exacerbated by the trend towards an ageing working population. European legislation is pressing for improved working conditions to eliminate the risks associated with health problems for workers. For this reason, the application of ergonomics in this field is growing. Musculoskeletal disorders, which are most often ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…At this stage, the conceptual approach involves integrating research findings, interpreting data, and forming a cohesive conclusion. Researchers must ensure that the [51], [52], [39] [53], [54], [45] [46], [48], [49] [40], [55], [56] [50], [57], [58] [42], [59], [60] [61], [43] synthesis of findings is based on the conceptual framework developed earlier and is relevant to the research questions.…”
Section: ) Phase 4: Synthesis Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, the conceptual approach involves integrating research findings, interpreting data, and forming a cohesive conclusion. Researchers must ensure that the [51], [52], [39] [53], [54], [45] [46], [48], [49] [40], [55], [56] [50], [57], [58] [42], [59], [60] [61], [43] synthesis of findings is based on the conceptual framework developed earlier and is relevant to the research questions.…”
Section: ) Phase 4: Synthesis Of Findingsmentioning
confidence: 99%
“…Integrating technology that understands context can enhance the system's ability to recognize movements in different situations, whether in a virtual environment or the real world. The development of smaller, lighter, and portable MoCap sensors can improve accessibility and enable their use in various contexts and locations [51], [52], [53], [54], [46], [40], [59], [61]. These challenges, along with other issues such as the need for accurate calibration and noise mitigation in data, create complexity in developing an effective and accurate MoCap system for 3D animation.…”
Section: ) Advancements In Motion Capture Technologymentioning
confidence: 99%
“…However, there is a high degree of subjectivity in the risk assessment. Motion capture kinematic suits, motion sensors applied on the body can ensure the objectivity of the assessment [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The MMH ergonomic assessment is carried out in an observational manner using the NIOSH method to calculate the risk indices. A digital ergonomic assessment is fundamental to deliver a more consistent risk evaluation [19][20][21][22]. From the literature, several works [22][23][24] aim to evaluate the ergonomic risk associated with the upper limbs for human-robot interaction purposes.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, several works [22][23][24] aim to evaluate the ergonomic risk associated with the upper limbs for human-robot interaction purposes. Some studies provide an online risk evaluation, but they use equipment that is not well suited for real adoption in industrial scenarios, such as force sensors to calculate ground reaction forces [20], high-resolution cameras for motion capture [19], or box sensing to track the movement of boxes [25]. More recently, Lorenzini et al [26] have suggested evaluating ergonomic risk factors using robotics-inspired indices.…”
Section: Introductionmentioning
confidence: 99%